Minimizing coliform and Escherichia coli bacteria in clean water through a chlorine diffuser method combined with black sand - Eka Nurul Fathonah; Rezania Asyfiradayati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Indonesia's 2016 health profile shows that the percentage of households with access to drinking water and potable water in Central Java Province is 75.88%, leaving 24.2% of the population without adequate drinking water sources. High concentrations of total Coliform are an indicator of pathogenic contamination that can lead to the spread of waterborne diseases. Contamination from E. coli and coliform bacteria in clean water sources can cause diarrhea if consumed. Purpose: To assess the effectiveness of the chlorine diffuser method combined with black sand in reducing Coliform and Escherichia coli levels in clean water. Method: A quantitative descriptive approach with a quasi-experimental design. Samples were collected four times over a ten-day period, with bacterial levels measured before and after treatment at intervals of 30 minutes, 45 minutes, and 60 minutes. The study utilized a chlorine diffuser as the primary research instrument. Data collection methods included direct observation and the compilation of both primary and secondary data. Laboratory testing of the samples was performed using the compact dry method, followed by univariate analysis to evaluate the effectiveness of the chlorine diffuser in reducing coliform bacteria in groundwater wells. Results: Univariate analysis showed that before treatment, the coliform bacteria level was 60 CFU/100 ml. After treatment, the levels were 40 CFU/100 ml after 30 minutes, 45 CFU/100 ml after 45 minutes, and 40 CFU/100 ml after 60 minutes of contact time. For E. coli, the bacteria level before treatment was 3 CFU/100 ml. After treatment, it was 0 CFU/100 ml with 30 minutes of contact, 1 CFU/100 ml with 45 minutes of contact, and 1 CFU/100 ml with 60 minutes of contact. Bivariate analysis showed a significant difference in Coliform levels based on treatment duration, with a significance value of 0.014. However, no significant difference was observed in E. coli levels, with a significance value of 0.168. Conclusion: The combination of the chlorine diffuser method and black sand effectively reduced coliform bacteria levels to meet environmental health standards. However, this method was less effective in eliminating Escherichia coli within the same treatment duration.